KEMAMPUAN PRODUKSI FONOLOGIS BAHASA INDONESIA ANAK PENYANDANG DOWN SYNDROME DI SDLB BANYUWANGI - Herlina Oktaviani; Asrumi Asrumi; Agustina Dewi Setyari (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2019)
This study examines the ability of phonological production or the ability to produce language sounds, namely vowels and consonants in Indonesian with Down syndrome, a student of the Banyuwangi An-Moerty Extraordinary Primary School. Phonological sensitivity has an important role in communicating creativity, including for persons with disabilities. The purpose of this study is to describe phonological production capabilities, and to find out the causes of the inability to pronounce language sounds of persons with Down syndrome, Bagus Chandra. This research is a qualitative research. This research data in the form of words spoken by Bagus Candra collected by the method of observation or observation with note-taking techniques and data in the form of information from the people closest to home and school were collected by interview method with note-taking techniques. Language data that have been classified are analyzed by distributional methods or agih methods with basic BUL techniques and advanced techniques: skipping, replacing, inserting, and changing the meanings, while data in the form of information are analyzed by descriptive analytical methods. The results of this study indicate that Bagus Chandra's phonological production ability in producing vowel sounds and consonant sounds is mostly perfect, because all vowel sounds [a], [i], [u], [e], and [o], and consonant sounds which includes sounds [b], [c], [d], [g], [h], [j], [k], [l], [m], [n], [p], [q] , [s], [t], and [y] can be pronounced correctly without obstacles. In this case, only a small part of the consonant sound, namely: sounds [r], [f], [v], [w], [x], and, [z] cannot be pronounced perfectly. Physically, the inability is caused by abnormal growth of the tongue, which is the size of the tongue that is longer and wider, and often extended.